Exploring cognitive load and emotional states for the visually impaired - Afroz, Sharmin; Shimanto, Zubaed Hassan; Jahan, Ra qua Sifat (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2019.